A comparison of control systems for the flight transition of VTOL unmanned aerial vehicles - Kriel, Steven Cornelius (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2009.